Pengaruh Effervescent Ekstrak Kulit Manggis (Garcinia Mangostana L.) sebagai Denture Cleanser terhadap Kekuatan Transversal Termoplastik Nilon - S, Rudy; Arifin, Nafilah Novianti; Mayangsari, Nino; Septommy, Catur; Gustina, Mara Gustina; Setiawati, Herautami Caesar Yulia (Bhakta Dental Journal, 2025)
Background: Thermoplastic nylon is a flexible denture base. Denture base strength was measured by transverse strength test. A natural Denture Cleanser can be made from mangosteen peel extract. Mangosteen peel extract has antibacterial and antifungal properties so it can be used as a cleaning medium for nylon thermoplastic dental plates. Purpose: To determine the effect of soaking effervescent mangosteen rind extract (Garcinia mangostana L.) with concentrations of 30% and 60% as a Denture Cleanser on the transverse strength of thermoplastic nylon. Methods: True experimental laboratory research with a post test only control group design. This study used nylon thermoplastic samples with a total of 24 samples divided into 4 groups, namely control group (-), control (+), treatment 1 (30% mangosteen effervescent extract), and treatment 2 (60% mangosteen Effervescent extract). Results: The Shapiro-Wilk test showed results that were not normally distributed because the sig values ​​of the control group (-), control (+), and 60% mangosteen extract had a p value <0.05. In the homogeneity test between homogeneous groups. Then proceed with non-parametric statistical tests using the Kruskal Wallis test showing a p value <0.05. Conclusion: There is an effect of effervescent mangosteen rind extract (Garcinia mangostana L.) as a Denture Cleanser on the transverse strength of thermoplastic nylon. Keywords: Mangosteen Peel Extract, Denture Cleanser , Thermoplastic Nylon, Transverse Strength.